2023
DOI: 10.1186/s12891-023-06287-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in older women and level of agreement between the diagnostic instruments proposed by the European Working Group on Sarcopenia in Older People 2 (EWGSOP2)

Abstract: Background The European Working Group on Sarcopenia in Older People 2 (EWGSOP2) proposed the use of different diagnostic tools to assess sarcopenia. This study aimed to determine prevalence rates of sarcopenia according to the diagnostic instruments proposed by EWGSOP2 and to assess their level of agreement in older Brazilian women. Methods A cross-sectional study with 161 community-dwelling older Brazilian women. Probable sarcopenia was assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Although the isokinetic assessment showed a positive high correlation with the 5-SSt ( 33 ), it may reflect different results in terms of muscle function according to the sex and age of the sample. In another study, similarly to our findings, no concordance was reported between the two screening tests (5-SSt and HGS) for detecting probable sarcopenia in non-obese Brazilian older females ( 34 ). The authors suggested that this could be because HGS is a more specific test for assessing strength in the upper limbs, while the 5-SSt evaluates the strength of lower limbs and is commonly used as a proxy measure for physical performance.…”
Section: Discussionsupporting
confidence: 80%
“…Although the isokinetic assessment showed a positive high correlation with the 5-SSt ( 33 ), it may reflect different results in terms of muscle function according to the sex and age of the sample. In another study, similarly to our findings, no concordance was reported between the two screening tests (5-SSt and HGS) for detecting probable sarcopenia in non-obese Brazilian older females ( 34 ). The authors suggested that this could be because HGS is a more specific test for assessing strength in the upper limbs, while the 5-SSt evaluates the strength of lower limbs and is commonly used as a proxy measure for physical performance.…”
Section: Discussionsupporting
confidence: 80%
“…as an important measure for the diagnosis of malnutrition and the assessment of muscle mass in the Global Leadership Initiative on Malnutrition (GLIM) standards and the European Working Group on Sarcopenia in Older People (EWGSOP) guidelines [40]. However, handgrip strength can only re ect muscle mass and cannot completely replace sarcopenia, and further assessment of other related indicators of sarcopenia is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for the study was estimated to ensure reliable prevalence estimates and adequate power for identifying risk factors for sarcopenia. Based on previous studies [ 13 ], an adjustment factor was applied to account for potential non-response and dropouts. We estimated a 30% non-response rate.…”
Section: Methodsmentioning
confidence: 99%